Investigation of Pre-School Childrens’ Self-Concept in terms of Emotion Regulation Skill, Behavior and Emotional Status - Arslan, Emel (Anales de Psicología / Annals of Psychology, 2021)
The purpose of the present research is presenting the predictor relations between self-concept, emotion regulation, behaviour and emotional state among 5-6 years old children and test the model set in accordance with these relationships. The present research adopted the relational screening model, which is a sub-type of general screening model. The work group of the research consists of 136 male, 127 female, the total of 263 students, who were selected among students of various pre-schools. Data collection tools utilized for the present research are Purdue Self Concept Scale For Preschool (PSCS), Emotion Regulation Checklist (ERC) and Preschool Behavioural and Emotional Rating Scale (PreBERS). Structural equation modelling analysis was conducted to present the predictor relationships between self, emotion regulation, behaviour and emotional state among pre-school students and to investigate their effects. Structural equation modelling analysis was conducted in AMOS 19 software program. In the final model obtained in the present research (X2 = 201.711, df = 71, p < .001), there were four exogenous (physical, academic, social and mother acceptance) and six endogenous behaviour and emotional state, emotion regulation (dz, oh, sg, aao, emotion regulation and variability negativity) data. The Bentler-Bonett normed fit index (NFI), The Tucker-Lewisco efficient fit index (TLI) and other fit indices showed that the model presented a good fit. According to the findings obtained with predictor relationships, there was a positive linear relationship between self and behaviour and emotional state and there was a positive linear relationship between self-concept and emotion regulation among pre-school students.